Using a practical molecular capsular serotype prediction strategy to investigate Streptococcus pneumoniae serotype distribution and antimicrobial resistance in Chinese local hospitalized children - Jin, Ping (BMC Pediatr, 2016)
BACKGROUND: China is one of ten countries with the highest prevalence rate of pneumococcal infections. However, there is limited serotype surveillance data for Streptococcus pneumoniae, especially from the community or rural regions, partly due to limited serotyping capacity because Quellung serotyping is only available in few centers in China. The aim of this study was to develop a simple, practical and economic pneumococcal serotype prediction strategy suitable for future serotype surveillance in China. METHODS: In this study, 193 S. pneumoniae isolates were collected from hospitalized children, 96.9 % of whom were < 5 years old. The cpsB sequetyping, complemented by selective and modified USA CDC sequential multiplex-PCR, was performed on all the isolates, and serotypes 6A-6D specific PCRs were done on all serogroup 6 isolates. Based on systematic analysis of available GenBank cpsB sequences, we established a more comprehensive cpsB sequence database than originally published for cpsB sequetyping. Antibiotic susceptibility of all isolates was determined using the disk diffusion or E-test assays. RESULTS: We built up a comprehensive S. pneumoniae serotype cpsB sequetyping database for all the 95 described serotypes first, and then developed a simple strategy for serotype prediction based on the improved cpsB sequetyping and selective multiplex-PCR. Using the developed serotype prediction strategy, 191 of 193 isolates were successfully “serotyped”, and only two isolates were “non-serotypeable”. Sixteen serotypes were identified among the 191 “serotypeable” isolates. The serotype distribution of the isolates from high to low was: 19 F (34.7 %), 23 F (17.1 %), 19A (11.9 %), 14 (7.3 %), 15B/15C (6.7 %), 6B (6.7 %), 6A (6.2 %), 9 V/9A (1.6 %); serotypes 6C, 3, 15 F/15A, 23A and 20 (each 1.1 %); serotypes 10B, 28 F/28A and 34 (each 0.5 %). The prevalence of parenteral penicillin resistance was 1.0 % in the non-meningitis isolates and 88.6 % in meningitis isolates. The total rate of multidrug resistance was 86.8 %. CONCLUSIONS: The integrated cpsB sequetyping supplemented with selective mPCR and serotypes 6A-6D specific PCRs “cocktail” strategy is practical, simple and cost-effective for use in pneumococcal infection serotype surveillance in China. For hospitalized children with non-meningitis penicillin-susceptible pneumococcal infections, clinicians still can use narrow-spectrum and cheaper penicillin, using the parenteral route, rather than using broader-spectrum and more expensive antimicrobials. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12887-016-0589-7) contains supplementary material, which is available to authorized users.